Desenvolvimento da sistematização da identidade conceitual e visual da marca Rose Petenucci - Meissner, Andressa Petenuci (2013)
The study conducted throughout this paper aimed to understand and develop the appropri- ate identity guide to Rose Petenucci’s brand. The proposal was developed with the goal of structure a new possibility for the company communication management, focused on contemporary trends that explore more than just utilitarian and aesthetic aspects of the brand’s components. The systematization and documentation of the main elements that compose the strategic basis, and experiential imagery took aim at standardizing the brand as a whole. Since the identity management deals with visual and sensory elements that became an extremely, powerful and strong source of the impressions perceived by the customer. Given this perspective, was also aimed the brand experience valorization, as it is become one of the greatest differential when works customer engagement through concrete and real experiences providing the construction of a solid and conscious relationship influential enough to create a bond of loyalty between the audience and the brand.